The Challenges of Preserving the Kasepuhan Karang Indigenous Forest and Its Strategic Role in Addressing Climate Change - Dirkareshza, Rianda; Sadiawati, Diani; Syahuri, Taufiqurrohman; Fauzan, Muhammad; Maula, Putri Ni'matul; Tobing, Vania Athalia Lumban (UNIVERSITAS PAKUAN, 2025)
Kasepuhan Karang is one of the Sundanese indigenous communities located in the Lebak Regency, Banten Province, Indonesia. This community is part of a network of kasepuhan around the Gunung Halimun Salak National Park (TNGHS). Their lives are closely related to environmental sustainability, especially in the management of customary forests. The social and cultural systems of the Kasepuhan Karang community reflect harmony between humans and nature. These values are reflected in customary traditions such as ngaseuk (planting), customary spatial planning that divides the area into restricted forests, production forests, and agricultural land, as well as tatali paranti (customary rules) that serve as guidelines for maintaining ecosystem sustainability. This study focuses on the importance of the Kasepuhan Karang Customary Forest in the context of environmental conservation and climate change mitigation. In addition, this study will identify the main challenges faced in preserving customary forests, including policy aspects, cross-sectoral understanding, and external pressures that threaten their sustainability. By prioritizing the perspective of indigenous peoples as the primary managers of the forest, this study aims to provide an overview of how synergy between local traditions and modern policies can be realized to support sustainable development.